Cranial acetabular osteophytes limits the maximal amplitude of hip abduction - amaro, a (2007)
The aim of this study was to establish a relationship between the existence of cranial acetabular osteophytes (CAO) in hip joints showing varying degrees of degenerative alterations and the range of maximal hip abduction. Seventy-six hip joints from 38 patients (42 82 years old) expecting hip joint replacement because of primary osteoarthritis (OA) were examined; out of those, 50 hip joints showed different levels of OA according to the American College of Rheumatology criteria. The radiological evaluation included the measurement of the length of the CAO and the amplitude of "free angle'' (FA, centered in the femoral head), remaining between the lateral extremity of the CAO and the point where the femoral neck would hit the CAO during abduction. The range of passive motion (ROPM) for abduction was assessed using a goniometer. The correlation between abduction and radiological alterations was calculated with the Pearson coefficient. ROPM in abduction was negatively correlated with the length of CAO (r = -0.50; P < 0.01) and positively correlated with the FA (r = 0.60; P < 0.01). The data suggest that the length of CAO plays a key role to limit the ROPM during abduction and that the length of CAO and FA may be useful measures to predict hip function during abduction.